2003
DOI: 10.1143/jjap.42.7209
|View full text |Cite
|
Sign up to set email alerts
|

Growth of ZnO on Si Substrate by Plasma-Assisted Molecular Beam Epitaxy

Abstract: Epitaxial ZnO films have been grown on Si(111) substrates by molecular beam epitaxy using oxygen plasma. An initial Zn layer deposition followed by its oxidation produces a superior template for the subsequent ZnO growth and a low-temperature ZnO buffer layer improves the structural and optical properties of ZnO films. As a result, we succeeded in growing highquality ZnO films directly on Si substrates. We observed cracks composed of straight lines along the principal axes of the Si(111) surface. These cracks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
3

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 6 publications
(8 reference statements)
2
30
3
Order By: Relevance
“…The results of the DCXRD measurements show that the as-grown ZnO film has high crystalline quality. Kawamoto et al [12] reported that epitaxial ZnO films have been grown on Si(1 1 1) substrates by molecular beam epitaxy using an oxygen plasma, and the thickness of the as-grown films were approximately 1.0 mm. The full-width at half-maximum (FWHM) of the ZnO(0 0 0 2) diffraction peak was 0.231 as measured by X-ray diffraction measurements.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of the DCXRD measurements show that the as-grown ZnO film has high crystalline quality. Kawamoto et al [12] reported that epitaxial ZnO films have been grown on Si(1 1 1) substrates by molecular beam epitaxy using an oxygen plasma, and the thickness of the as-grown films were approximately 1.0 mm. The full-width at half-maximum (FWHM) of the ZnO(0 0 0 2) diffraction peak was 0.231 as measured by X-ray diffraction measurements.…”
Section: Resultsmentioning
confidence: 99%
“…The use of an electrically conductive Si substrate can relieve this problem. Many deposition techniques have been developed to prepare ZnO thin films on Si substrates, such as plasmaenhanced chemical vapor deposition (PE-CVD) [6], pulsed laser deposition (PLD) [8], radio frequency (RF) sputtering [9], metalorganic vapor phase epitaxy (MOVPE) [10] chemical vapor deposition (MOCVD) [11], and plasma-assisted molecular beam epitaxy [12]. Research results show that the growth of epitaxial ZnO films directly on Si is a difficult task, because the Si substrate is easily oxidized and covered with a resulting amorphous SiO x layer when it is exposed to reactive oxygen sources [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we have focused on the Si substrates for the growth of ZnO films [16][17][18]. The growth of epitaxial ZnO films on Si is, however, known to be a difficult task because the Si substrate surface is easily oxidized and the crystal quality of ZnO film grown on such a SiO x layer is considerably deteriorated.…”
Section: Introductionmentioning
confidence: 99%
“…The growth of epitaxial ZnO films on Si is, however, known to be a difficult task because the Si substrate surface is easily oxidized and the crystal quality of ZnO film grown on such a SiO x layer is considerably deteriorated. In order to prevent the Si substrate surface from being oxidized in the initial growth stage of ZnO, and improve the crystal quality of ZnO films, we have used two methods: initial Zn layer deposition followed by its oxidation [16,17] and initial Mg layer deposition followed by MgO growth [18]. Although the grown ZnO films exhibit very high photoluminescence (PL) efficiency by using the former method, they suffer from high density of micro-cracks along the principal axes on the Si(1 1 1) surface probably caused by the difference in the thermal expansion coefficients between ZnO and Si.…”
Section: Introductionmentioning
confidence: 99%